China's integration into the world economy - Whalley, John (World Scientific, 2011)
This book discusses China's integration into the world economy, drawing on papers previously written by the editor. It focuses on strong trade growth, FDI inflows, innovation policy (including transfer of technology and intellectual property), the role of saving, and the accumulation of human capital. It also analyzes the quantitative significance of openness in driving China's growth. While other books on China do not focus much on China's integration into the world economy, this book provides technically strong analyses of key contributing factors to China's growth performance. It also highl.